Enhancing Problemsolving Skills in Mathematics Through Inquirybased Learning: A Case Study in High School Education - Novia Uma Khoirunnisa; M.Isbatul Haqi; Mohammad Sayful Anam (International Journal of Mathematics and Science Education, 2024)
This study explores the effectiveness of inquirybased learning (IBL) in enhancing problemsolving skills among high school students in mathematics. The research is based on a case study conducted in a school where IBL methods were incorporated into the curriculum. The findings suggest that students engaged in inquirybased activities showed improved critical thinking and problemsolving abilities compared to traditional teaching methods. This paper discusses the impact of IBL on students' motivation and their ability to approach complex mathematical problems with greater confidence.